Investigation of the post-cryogenic regeneration ability of potato varieties under different cultivation conditions - E. S. Bespalova; Yu. V. Ukhatova; N. N. Volkova; E. V. Oves; N. A. Gaitova; T. A. Gavrilenko (Вавиловский журнал генетики и селекции)
Cryopreservation provides long-term storage of the gene pool of potato varieties in cryobanks at extremely low temperatures. Currently, droplet vitrification is the most widely used method for cryopreservation of potato varieties, which is constantly improving to increase the regeneration rates of the stored plant material. Different modifications of this method are used in the world’s leading potato genebanks. This paper presents the results of studying the effect of cultivation conditions after plunging into liquid nitrogen and thawing of shoots tips and axillary buds of in vitro plants on their postcryogenic recovery. The droplet-vitrification method modified at VIR was used for cryopreservation. The factor “prolonged dark incubation of explants” did not have a significant effect on the frequency of post-cryogenic regeneration of the studied varieties except for one variety (Krepysh), for which a significant increase in the regeneration rate was observed for the shoot tips cultivated in the darkness compared to the cultivation under the photoperiod 16/8 hours (light/darkness). The frequency of post-cryogenic regeneration of shoot tips was higher than that of the axillary buds for all varieties; however, these differences were significant (p < 0.05) only in two cases: for the variety Udacha (a photoperiod of 16/8 hours) and for the variety Krepysh (the dark incubation). The results of two-factor analysis of variance indicate that there is no effect of interaction of factor 1 (prolonged dark incubation) and factor 2 (explant type) on the ability of varieties to post-cryogenic recovery. Taking into account the obtained results, the further cryopreservation of an extended subset of 9 varieties was carried out using shoot tips, which, after freezing-thawing, were cultivated under the photoperiod of 16/8 hours. The frequency of post-cryogenic regeneration of these varieties varied from 30 to 60 %. A significant effect of genotype on postcryogenic recovery has been established. The ability of varieties to regenerate shoots after freezing and thawing was not related to the values of morphogenic indices of in vitro plants. The age of the meriklons (2–4 years) did not significantly affect either the morphogenic indices or the frequency of post-cryogenic regeneration.